Firewood Trade in the Cucaita Town at the 1950’s - Vanegas-Toba, Elsa Yaneth (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article addresses, as a central theme, the firewood trade in the municipality of Cucaita in the 1950s. Its purpose is to show the economic, labor and social context of the population and, at the same time, the development of this economic activity. The economic activities of the Cucaitense population at the time, revolved around the agricultural sector, highlighting cereal crops such as wheat, barley and oats -these for the low and flat area-; in the moor, potato cultivation stood out and, to a lesser extent, livestock development. Hence, parallel to the firewood trade, that of other products such as toasted flours, cuchucos, eggs, milk, arepas and cheeses was also developed. Therefore, the methodological process unfolds from environmental history, from the testimonies of the inhabitants of the municipality, who manifest the importance of this economic activity to go through certain economic difficulties; Similarly, it refers to the environmental impact triggered by this type of trade, which still persists today.